Assessing the effect of organisational commitment on turnover intentions amongst Islamic bank employees - Carole Serhan; Nehmeh Nehmeh; Ibrahim Sioufi (ISRA International Journal of Islamic Finance, 2022)
Purpose - The research aims to test the links amongst Meyer and Allen's three levels of organisational commitment and the commitment's effect on reducing turnover intentions for Islamic bank (IB) employees during the lockdown caused by coronavirus disease (COVID-19). Design/methodology/approach - The research follows a variable-centred approach. Primary data are collected through a survey of 324 respondents comprising IB employees from three Arab countries, notably the United Arab Emirates (UAE), Lebanon and Oman. Exploratory factor analysis (EFA) and Cronbach's alpha test are conducted to test the construct validity, reliability and internal consistency of collected data. Descriptive statistics are used to interpret the data. Zero-order correlations, multiple regression analysis and Fisher's Z-test are applied to assess the interrelations of the various groups of variables and the determinants of turnover intentions. Findings - Results show that there is a high level of significant intercorrelation amongst affective, normative and continuance commitments as well as amongst organisational commitment, individual differences and turnover intentions for IB employees from the three studied Arab countries. The results confirmed that turnover intentions are minimised in the presence of all three organisational commitment subscales and that individual differences amongst IB employees and organisational efficiency moderate the relationship between organisational commitment and turnover intentions. Originality/value - There is no empirical work that has been done on the determinants of turnover intentions amongst IB employees during the lockdown. This is valuable to organisational behaviour scholars and practitioners who are interested in the role that organisational commitment plays in IB's employment behaviour.
Keywords: 330; Individual differences; Islamic bank; Organisational commitment; Organisational efficiency; Turnover intentions